Molecular characterization of the TUBG1 meshwork's influence on Cytoskeletal organization - Darina Malycheva; Maria Alvarado-Kristensson (Heliyon)
The γ-tubulin (TUBG) meshwork is a central regulator of cellular architecture, orchestrating processes such as microtubule nucleation, mitochondrial organization, and genomic integrity. This study investigates the molecular impact of TUBG depletion on the cytoskeleton. Knockdown of TUBG using single guide RNA disrupted microtubule, vimentin, and lamin B networks while simultaneously reinforcing actin filaments structures. These findings suggest that actin reinforcement may act as a compensatory response to the broader disruption of cytoskeletal integrity. Expression of N-terminal (TUBG1-335) or C-terminal (TUBG334-451) fragments of TUBG1 partially restored these networks, with the C-terminal fragment demonstrating greater effectiveness reestablishing microtubule integrity. Both fragments stabilized vimentin filaments and the nuclear envelope, underscoring TUBG's dual structural and regulatory roles across multiple cytoskeletal systems. This study highlights the critical hubbing properties of TUBG in coordinating cytoskeletal integrity and its potential as a therapeutic target in cytoskeleton-related disorders.